Systemic Risk: A Comparative Study between Public and Private Banks - Mselmi, Aymen; Mahmoud, Imen (International Journal of Economics and Financial Issues, 2023)
This paper aims to study the capital insufficiency in various Tunisian banks which are on the list of the Tunisian stock exchange market. Basing our work on the various measures of systemic risk, we have modeled the shortfall capital of the Tunisian banking sector in order to compare private banks and public ones in terms of exposure to systemic risk. We have also studied the effect of stock market shocks on the banks’ marginal expected shortfall. The results obtained show that the systemic risk for the period 2006 and 2013 is mainly conveyed by the three public banks.